Development of Interactive Audio-Visual Multimedia to Enhance Students’ Qur’anic Recitation Fluency and Tajwid Accuracy at SMP Unismuh Makassar - Fitriani Nurdin; Hamsu Abdul Gani; Abdul Hakim; Nurhikmah Hasyim (CV. Media Inti Teknologi, 2025)
Background: Qur’anic learning in schools still faces obstacles in improving students’ recitation fluency and tajwid accuracy. Observations at SMP Unismuh Makassar showed that 52.6% of students had difficulty understanding BTQ (Baca Tulis Qur’an) material when learning relied only on textbooks and teacher explanations, while 80% struggled to study independently. Most students, however, supported the use of interactive multimedia, indicating the need for more engaging and accessible learning media.Aims: This study aimed to develop interactive audio-visual multimedia to enhance students’ Qur’anic recitation fluency and tajwid accuracy and to assess its validity, practicality, and effectiveness.Methods: A Research and Development (R&D) approach was employed using the ADDIE model. Data were collected through observations, questionnaires, tests, and documentation, with using valid and reliable instruments.Result: The multimedia achieved high validity (98% material; 78% media), strong practicality (99% teacher; 89.6% students), and indicating strong effectiveness with an N-Gain score of 76.38%.Conclusion: This study offers an effective interactive multimedia model for improving Qur’anic recitation skills and supports student-centered learning.